Synopsis of Health Systems Research across the World Bank Group from 2000 to 2010 - Weber, Stephanie; Brouhard, Katherine; Berman, Peter (World Bank, Washington, DC, 2013)
Policymakers and researchers around the world are working to identify the 'how to' aspect of health systems strengthening. However, there is neither consistency nor clarity on what makes a 'good' health systems study with regard to research design, methodology, etc. This synopsis of health systems research carried out by the World Bank highlights the scale and scope of the Bank's knowledge contributions to this important field over the last 10 years. The authors hope this review will stimulate the Bank and other development partners to strengthen efforts to create knowledge to improve health systems. The purpose of this report is to describe the research on health systems that have taken place across the World Bank Group over the last 10 years. The World Bank is a big contributor to research on health systems. The search identified 664 reports, policy research working papers, discussion papers, books, book chapters, how-to manuals, guides, briefs, policy notes and journal articles on health systems published over the last 10 years. Health systems research is widely distributed across the Bank, and much of it is carried out by region-based staff and their colleagues and clients in countries. The Bank's health systems research covers a wide scope. The authors have considered work which is both problem-specific focused on specific diseases, health problems, or outcomes but with substantial health systems content as well as cross-cutting in terms of specific health system 'control knobs.' The authors lack a very precise definition of health systems. This review highlights the important contributions of the World Bank's partners. The Bank engages researchers in its client countries, partners from academic institutions, development agencies, and knowledge organizations.